Features of neuro-endocrine and immune reactions to various water-salt loads in female rats - Gozhenko, Olena A; Zavidnyuk, Yuriy V; Korda, Mykhaylo M; Mysula, Igor R; Klishch, Ivan M; Zukow, Walery; Popovych, Igor L (Journal of Education, Health and Sport, 2018)
Background. Previously, we have shown that the weekly load of rats with water-salt solutions of different chemical compositions causes both general and specific reactions of the parameters of metabolism. The purpose of this study is to identify under these conditions specific neuroendocrine and immune responses. Materials and methods. Experiment was performed on 58 healthy female Wistar rats 240-290 g divided into 6 groups. Animals of the first group remained intact, using tap water from drinking ad libitum. Instead, the other rats received the same tap water as well as waters Sophiya, Naftussya, Gertsa and its artificial salt analogue through the probe at a dose of 1,5 mL/100 g of body mass for 6 days. The day after the completion of the drinking course in all rats some neuroendocrine and immune parameters were registered. Results. The method of discriminant analysis revealed 29 parameters of the neuroendocrine-immune complex (10 of them reflect the neuroendocrine regulation, 4 thymus mass and thymocytogram elements, 5 elements of splenocytogram, 10 elements of immunocytogram and leukocytogram of blood and parameters of phagocytosis), according to which the reaction on various water-salt loads are identified with an accuracy of 98.3%. Conclusion. The peculiarities of the reactions of the parameters of the neuroendocrine-immune complex are due to the content of water in sulfate, bicarbonate and magnesium, as well as organic carbon and nitrogen.